Membrane Microreactors for the On‐Demand Generation, Separation, and Reaction of Gases. Issue 58 (11th September 2020) - Hone, Christopher A.; Kappe, C. Oliver
Abstract: The use of gases as reagents in organic synthesis can be very challenging, particularly at a laboratory scale. This Concept takes into account recent studies to make the case that gases can indeed be efficiently and safely formed from relatively inexpensive commercially available reagents for use in a wide range of organic transformations. In particular, we argue that the exploitation of continuous flow membrane reactors enables the effective separation of the chemistry necessary for gas formation from the chemistry for gas consumption, with these two stages often containing incompatible chemistry. The approach outlined eliminates the need to store and transport excessive amounts of potentially toxic, reactive or explosive gases. The on‐demand generation, separation and reaction of a number of gases, including carbon monoxide, diazomethane, trifluoromethyl diazomethane, hydrogen cyanide, ammonia and formaldehyde, is discussed. Abstract : Go with the flow : Gas–liquid transformations are very important for organic synthesis. However, gases can be very challenging to use at laboratory scale. Continuous flow membrane reactors enable the safe on‐demand laboratory‐scale generation, separation, and reaction of gases without the need for distillation or gas cylinders.